GAMBARAN POLA MAKAN DAN AKTIVITAS FISIK PENDERITADIABETES MELLITUS DI RW 01 KELURAHAN JAGIR SURABAYA - Novera Herdiani (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
Diabetes Mellitus (DM) is a group of hitrogen disorder characterized by the increased of bloodglucose level or hyperglycemia. It was reported from WHO that population study of Diabetes Mellitusin various countries, the number of Diabetes Mellitus patients in 2000 in Indonesia got the biggest4th rank of the Diabetes Mellitus patients number with prevalence of 8.4 million inhabitants. HandlingDiabetes Mellitus sufferers is a lifelong responsibility. Therefore, handling Diabetes Mellitus needsinitiative and regularity so all sufferers should understand how to run diet and exercise to control thedisease. The purpose of this study is to find out the description of eating and physical activity patternsof Diabetes Mellitus sufferers in RW 01, Kelurahan Jagir Surabaya. The design of the study used wascross-sectional, the sample was 56 people which selection was carried out by sampling techniqueused a Consecutive Sampling. The variable in this study was eating and physical activity patterns ofDiabetes Mellitus patients. The data were collected through questionnaires, then the statistical datawere processed descriptively by using common and frequency distribution tables used scoring datacollection procedures. The result of the study of Eating pattern of Diabetes Mellitus sufferers, 54%of the patients had lack of the calories needs in a day, based on the fulfillment of the diet schedule,more than half diabetics (70%) did not conduct an eating schedule and based on the consumption ofsweet foods (68%) diabetics consumed food sweet. The result of physical activity of the diabeticswhose age was <30 years was varied 33.33% with the result of less physical activity and optimalphysical activity as 4 people (57.14%) were college educated. The result which was varied that 50%had high school education with less physical activity, while the patients whose education waselementary and junior high had physical activity minimally. Based on the result, it is concluded thatall Diabetes Mellitus sufferers (100%) have not met a good eating pattern, physical activity patternsof Diabetes Mellitus patients (30%) have` less physical activity.